Hedonic Shopping Value Analysis on Impulse Buying With Shopping Lifestyle As A Mediating Variable - Edho Valdano Putra; Erick Karunia; Tinik Sugiati; Mappa Panglima Banding (Fakultas Ekonomi, Universitas Muslim Indonesia, 2026)
This study aims to analyze the effect of Hedonic Shopping Value on Impulse Buying with Shopping Lifestyle as a mediating variable among Shopee users in North Kalimantan Province. The research background is the growing prevalence of impulsive purchasing behavior in e-commerce, driven by hedonic shopping experiences, interactive digital platform features, and changes in consumer lifestyles. This study employs a quantitative approach, using a survey of 150 Shopee users across regencies and cities in North Kalimantan. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among variables. The results show that Hedonic Shopping Value has no significant direct effect on Impulse Buying but does have a positive and significant effect on Shopping Lifestyle. Furthermore, Shopping Lifestyle has a significant positive effect on Impulse Buying and fully mediates the relationship between Hedonic Shopping Value and Impulse Buying. These findings indicate that momentary emotional stimuli do not merely drive impulsive buying behavior; they are also strongly influenced by consumers’ shopping lifestyles shaped within the e-commerce ecosystem. Theoretically, this study contributes to the development of digital consumer behavior literature. At the same time, it offers practical implications for e-commerce platforms in designing hedonic shopping experiences that foster sustainable shopping lifestyles.